SCIENTIFIC AND PRACTICAL JUSTIFICATION OF TECHNOLOGY TO IMPROVE WATER-SALT REGIME IN AERATION ZONE OF ARID TERRITORIES - Muradov, Shuhrat Odilovich; Turdiyeva , Feruza Alisherovna (Educational Research in Universal Sciences, 2023)
The necessity of the use of subirrigation in arid territories is motivated on the base of experimental-theoretical researches. The principles of the calculation of the device were stated for regulating the drainage sewer. The way of the cascade building of the device was offered. The results of the research permit to raise water supply of the irrigated lands and to improve the water-salt regime of the aeration zones.